Please help explain why

z spread > nominal spread => upward sloping yield curve

z spread < nominal spread => downward sloping yield curve

Thank you very much

Please help explain why

z spread > nominal spread => upward sloping yield curve

z spread < nominal spread => downward sloping yield curve

Thank you very much

Anyone help please

The algebra can be fairly complicated.

Will an algebraic proof really help solidify the idea for you?

Thanks S2000

I just want to find any logic here to remember it easily rather than learning by heart

Youâ€™re welcome.